The Solow residual, a distributional approach: The case of Chile, 1985-2019 - Fernando Villanueva Melo (PSL Quarterly Review)
The primary goal of this paper is to present a distributive proposal for reinterpreting Solow’s residual and apply it within the Chilean context. We argue that Solow’s residual can only indirectly capture technological phenomena. This critique draws upon the contribution of Felipe and McCombie (2020), who contend that production functions merely reflect an identity account. Hence, the so-called Total Factor Productivity (TFP) mirrors the dynamic of real wages and the rate of profit.